Learning advertising text using Canva media at junior high school - Putra, Muhammad Yani; Prasetyo, Sri Kukuh; Raditya, Ria; Astuti, Ariesty Fuji; Ekici, Gail (International Journal on Education Insight, 2023)
This research aims to describe the use of Canva media in Indonesian language learning, especially advertising text materials, slogans, and posters for eighth-grade students of junior high school. This research used a descriptive qualitative method to figure out how the use of Canva could impact on the students’ performance during the classroom session. The subjects in this research were 32 eighth-grade students at SMP Negeri 5 Yogyakarta, a public junior high school located in Yogyakarta, Indonesia. The findings provides the insights that the use of Canva media in learning advertising texts, slogans, and posters can improve the students’ learning outcomes, thinking skills, and their ability to master digital technology at the learning.